2017
DOI: 10.3892/mmr.2017.6236
|View full text |Cite
|
Sign up to set email alerts
|

The role of ZFP580, a novel zinc finger protein, in TGF-mediated cytoprotection against chemical hypoxia-induced apoptosis in H9c2 cardiac myocytes

Abstract: Zing finger protein 580 (ZFP580) is a novel Cys2-His2 zinc-finger transcription factor that has an anti-apoptotic role in myocardial cells. It is involved in the endothelial transforming growth factor-β1 (TGF-β1) signal transduction pathway as a mothers against decapentaplegic homolog (Smad)2 binding partner. The aim of the present study was to determine the involvement of ZFP580 in TGF-β1-mediated cytoprotection against chemical hypoxia-induced apoptosis, using H9c2 cardiac myocytes. Hypoxia was chemically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…[23][24][25]54,55 These lead to the hydroxylase enzyme inactivation, hypoxia-inducible factor HIF-1α stabilization, ROS generation, apoptosis and increased Bax/Bcl-2 ratio followed by activation of caspase-3 cleavage. 55,56 The data obtained in the present study on H9c2 cells confirmed the reduction in Cnx43, KCNQ1 and Bcl-2 expression following exposure to the hypoxia-mimetic agent, while treatment with telmisartan restored them. This in line with other experiences showing that angiotensin II (ATII) exerts an inhibitory effect on Cnx43, KCNQ1 and Bcl-2 expression, and PPAR-γ agonism is effective in preventing the reduction in Cnx43 induced by ATII.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[23][24][25]54,55 These lead to the hydroxylase enzyme inactivation, hypoxia-inducible factor HIF-1α stabilization, ROS generation, apoptosis and increased Bax/Bcl-2 ratio followed by activation of caspase-3 cleavage. 55,56 The data obtained in the present study on H9c2 cells confirmed the reduction in Cnx43, KCNQ1 and Bcl-2 expression following exposure to the hypoxia-mimetic agent, while treatment with telmisartan restored them. This in line with other experiences showing that angiotensin II (ATII) exerts an inhibitory effect on Cnx43, KCNQ1 and Bcl-2 expression, and PPAR-γ agonism is effective in preventing the reduction in Cnx43 induced by ATII.…”
Section: Discussionsupporting
confidence: 81%
“…Ventricular H9c2 cells are a well‐known relevant cell model in the mimicking of IR injury: Being the closest cells to primary cardiomyocytes concerning their energy metabolism features, such as number and arrangements of mitochondria and presence of beta‐tubulin II, H9c2 cells are a simple validated and useful in vitro model for exploring the mechanisms driven by hypoxia/reoxygenation . These lead to the hydroxylase enzyme inactivation, hypoxia‐inducible factor HIF‐1α stabilization, ROS generation, apoptosis and increased Bax/Bcl‐2 ratio followed by activation of caspase‐3 cleavage …”
Section: Discussionmentioning
confidence: 99%
“…Propofol protects against CoCl 2 -induced cardiac cell apoptosis. CoCl 2 has been reported to induce apoptosis of rat cardiac H9C2 cells (22). Therefore, the present study used Annexin V/PI staining to investigate the apoptotic ratio of AC16 and HCM cells following different treatments (Fig.…”
Section: Propofol Increases Cardiomyocyte Viability and Inhibitsmentioning
confidence: 99%
“…MTT was added at a final concentration of 25 mg/ml. After a 4-h incubation at 37˚C, the reaction was halted by adding 150 µl of dimethyl sulfoxide (DMSO), and the relative absorbance value (AV) was measured at 595 nm using a microplate reader [21]. Cell viability was calculated according to the AV and density of cells.…”
Section: Cell Viability Assessment Under Various Hypoxic Conditionsmentioning
confidence: 99%